Achieving Higher Quality Levels for Information Systems Project Management (The International Journal for Scientific Research, 2023)
This paper aims to achieve higher quality levels for information systems project management through proposing a quality assurance model for Information Systems Projects Management (IS-PM). This paper presents important quality concepts and fundamentals related to IS-PM. In addition, it presents the life cycle, phases, and activities of IS-PM. Depending on the proposed steps and a combination of statistical techniques, this paper introduces a proposed quality assurance model for IS-PM activities. This proposed model can be used for building a software tool for the quality assurance of IS-PM.
Keywords: Quality Assurance; Information Systems Projects Management; Quality Control